Non-Invasive Prostate Cancer Characterization with Diffusion-Weighted MRI: Insight from In silico Studies of a Transgenic Mouse Model - Hill, Deborah K.; Heindl, Andreas; Zormpas-Petridis, Konstantinos; Collins, David J.; Euceda, Leslie R.; Rodrigues, Daniel N.; Moestue, Siver A.; Jamin, Yann; Koh, Dow-Mu; Yuan, Yinyin; Bathen, Tone F.; Leach, Martin O.; et al. (Frontiers in Oncology, 2017)
Diffusion-weighted Magnetic Resonance Imaging (DWI) enables non-invasive, quantitative staging of prostate cancer via measurement of the Apparent Diffusion Coefficient (ADC) of water within tissues. In cancer, more advanced disease is often characterised by higher cellular density (cellularity), which is generally accepted to correspond to a lower measured ADC. A quantitative relationship between tissue structure and in vivo measurements of ADC has yet to be determined for prostate cancer. In this study we establish a theoretical framework for relating ADC measurements with tissue cellularity and the proportion of space occupied by prostate lumina, both of which are estimated through automatic image processing of whole-slide digital histology samples taken from a cohort of six healthy mice and nine transgenic adenocarcinoma of the mouse prostate (TRAMP) mice. We demonstrate that a significant inverse relationship exists between ADC and tissue cellularity that is well characterised by our model, and that a decrease of the luminal space within the prostate is associated with a decrease in ADC and more aggressive tumour subtype. The parameters estimated from our model in this mouse cohort predict the diffusion coefficient of water within the prostate tissue to be 2.18 × 10−3 mm2 /s (95% CI: 1.90, 2.55). This value is significantly lower than the diffusion coefficient of free water at body temperature suggesting that the presence of organelles and macromolecules within tissues can drastically hinder the random motion of water molecules within prostate tissue. We validate the assumptions made by our model using novel in silico analysis of whole-slide histology to provide the simulated ADC (sADC); this is demonstrated to have a significant positive correlation with in vivo measured ADC (r2= 0.55) in our mouse population. The estimation of the structural properties of prostate tissue is vital for predicting and staging cancer aggressiveness, but prostate tissue biopsies are painful, invasive, and are prone to complications such as sepsis. The developments made in this study provide the possibility of estimating the structural properties of prostate tissue via non-invasive virtual biopsies from MRI, minimising the need for multiple tissue biopsies and allowing sequential measurements to be made for prostate cancer monitoring.